Pengaruh Komite Audit, Asimetri Informasi, Ukuran Perusahaan, Pertumbuhan Laba Dan Profitabilitas Terhadap Kualitas Laba (Studi Pada Perusahaan Manufaktur yang Terdaftar di BEI 2009-2010) - Arief Reyhan; Zirman '; Nur Azlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research is aims to detemine The influence of the audit committee,information assymmetry, size of the company,p rofit growth and profitability to the quality of earnings. The uadit committee of the measured variabels based on the number of member on the company, assymetry of information measured by the Bid ask spread, the size of company is measured by total asset log,profit growth id measured by subtracting the profit period right now with a profit of previous period are then divided by the previous period profit,profitability is measured using Return On Asset (ROA). Dependent variabel quality of profit measured by Ernings response Coefficient n(ERC). The research sample is a manufacturing company of 32 listings in BEI 2009-2010. And using sample techniques with purposive sampling. Multiple linear regression a statistical analysis using the enter methode to test examiine The influence of the audit committee,information assymmetry, size of the company,p rofit growth and profitability to the quality of Earnings. The result of this research show that only the size of the company, profit growth, profitability effect on the quality of Ernings.while the two other independent variable namely audit committee and assymetry information has no effect on the quality of earnings. This can be seen in the value of R Square is only 42,5 % means there is still other variable that have a relationship with the company’s earnings quality ammounted to 57,5 % which can be included in the next research.Keywords : Audit committee, The Information assymmetry, Size of the Company, Profit Growth, profitability , Quality of Ernings